The Power of Genetic Engineering in Revolutionizing Vaccines - Ramdas Bhat; Preeti Shanbhag; Sinchana S Bhat; Megha M; Kavana D K; Rithin K (International Journal of Vaccines, 2024)
Genetic engineering techniques, including recombinant subunit, viral vector, and nucleic acid vaccines have transformed the landscape of vaccine development. These novel approaches offer precise antigen design, enhanced safety profiles, and rapid adaptability to emerging pathogens. Key advantages include improved efficacy through targeted immune responses, increased safety due to the absence of live pathogens, and the ability to modify vaccines to address new variants or diseases quickly. Notable success stories, such as the hepatitis B vaccine and the recent mRNA-based COVID-19 vaccines, demonstrate the transformative potential of this technology. However, challenges persist in areas of production scalability, regulatory approval processes, and public perception. The effectiveness and broad acceptance of genetically modified vaccinations depend on resolving these problems. The field holds promising prospects for personalized vaccines tailored to individual genetic profiles, universal flu vaccines targeting conserved viral regions, and therapeutic vaccines for chronic diseases. As genetic engineering techniques continue to evolve, they have the potential to dramatically reshape our approach to disease prevention and treatment. This review explores the transition from conventional vaccine approaches to genetically engineered methods, examining their advantages, challenges, and future prospects. It aims to provide a comprehensive overview of how genetic engineering is revolutionizing vaccine development, offering hope for more effective, accessible, and adaptable solutions to global health challenges in the 21st century and beyond.
Keywords: Genetic engineering; Personalized medicine; Viral Vectors; global health; mRNA; vaccines